Ответы 2

  • 3х×2-7х+4=0

    6х-7х=-4

    -1х=-4

    х=-4:(-1)

    х=4

  • 3 {x}^{2}  - 7x + 4 = 0

    Д=

     {b}^{2}  - 4ac = 49 - 4 \times 4 \times 3 = 49 - 48 = 1

    x1,2 =  \frac{ - b +  -  \sqrt{1} }{2a}

    x1 =  \frac{7 + 1}{6}  =  \frac{8}{6}  =  \frac{4}{3}  =  1\frac{1}{ 3}

    x2 =  \frac{7 - 1}{6}  =  \frac{6}{6} = 1

    Ответ: 1, 1 1/3

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years